Evaluasi Pengungkapan Akuntansi Lingkungandalam Perspektif PT Timah (Persero) Tbk - Rosinta Ria; Holly Deviarti (Bina Nusantara University, 2012)
Timah is the pride of the province of Bangka Belitung and its society, despite the presence of Timah mining directly harmful to the environment such as forests and water pollution. Nevertheless, PT Timah is very popular with environmental preservation activities and empowering the local community. The purpose of this study is to evaluate environment preservation associated with financial reporting. The issue of Green Accounting will be very interesting if it is supported by qualitative data as evidence. Using the descriptive method, and data retrieval literature and interviews with community of Bangka Belitung, it can be concluded that PT Timah has good action up the environment. The results of this study will enhance a good image for PT Timah.